2006
DOI: 10.1007/s11258-006-9151-2
|View full text |Cite
|
Sign up to set email alerts
|

The Ups and Downs of Life on the Edge: The Influence of Water Level Fluctuations on Biomass Allocation in two Contrasting Aquatic Plants

Abstract: Plant communities at wetland edges typically exhibit strong zonation along water depth gradients, although community structure is not as simple as this common observation may suggest. Water levels fluctuate at many temporal scales and in varied patterns. Understanding of how water regime controls plant community structure requires information on how individual species are affected by water regime. The allocation of biomass to roots, tillers, stolons and inflorescences was measured over 16 weeks in two species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Wetland hydrologic regime can be described by two descriptors, namely, mean depth of standing water (the average aboveground water depth) and hydro-period (the percentage of time with the presence of standing water)-their combined use is found to be crucial to the study of plant response (Geoff et al, 2007). The two regimes used in the analysis below have 1 , which results in a wetter regime having mean standing water depth of 25 cm and being flooded 99% of the time.…”
Section: Parameterizations and Simulationsmentioning
confidence: 99%
“…Wetland hydrologic regime can be described by two descriptors, namely, mean depth of standing water (the average aboveground water depth) and hydro-period (the percentage of time with the presence of standing water)-their combined use is found to be crucial to the study of plant response (Geoff et al, 2007). The two regimes used in the analysis below have 1 , which results in a wetter regime having mean standing water depth of 25 cm and being flooded 99% of the time.…”
Section: Parameterizations and Simulationsmentioning
confidence: 99%
“…In wetlands, water depth directly influences the distribution, growth and suitability of specific species (Jackson and Colmer, 2005;Smith and Brock, 2007;Laitinen et al, 2008). Our study results showed that the biodiversity and coverage of macrophyte communities dominated by Phragmites australis reach their peaks at the water depths of -0.30 m and 0 m, respectively, and decrease either above or below that depth.…”
Section: Influence Of Water Depths On Plant Communitiesmentioning
confidence: 62%
“…0, 30 and 60cm at a high drawdown rate of 8cm/day. Studies of lower groundwater drawdown amplitudes (at 32cm) had demonstrated some degree of impact on wetland vegetation growth, in terms of root shoot ratio (Smith & Brock, 2007). In this experiment, drawdown was extended to 60cm below the initial water level and more rigorous measurements were applied.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated how wetland vegetation growth responds to controlled water level fluctuations, such as rate, frequency and depth of controlled flooding and drought conditions (Deegan et al, 2007;Smith & Brock, 2007;Wei et al, 2014). Deegan et al (2007) studied the impact of ±0cm, ±15cm, ±30cm and ±45cm…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation